Comparison of 800 Meter and 400 Meter Run Effects on The Increase Of Lactic Acid In Athletic Athlete - Barkah Sekar Kalih; Eka Anjar Rahmadani (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
This study aimed to obtain information about the differences in the increase in lactic acid from the 800 meter and 400-meter running results. Lactic acid is the result of the rest of the energy-burning metabolism of anaerobic lactated. This condition occurs in the metabolism of the breakdown of carbohydrates into lactic acid is not perfect, which is one indicator of the onset of fatigue in the muscles. The method used is two group pre-test and post-test design method. With purposive sampling technique, samples using 20 people from the population amount to 85 people from athletic KOP members of Jakarta State University. The data analysis technique used is an at-independent test. The data analysis technique used is a statistical technique with t-test significant t-significant = 0,05 data analysis technique used is t-test analysis to compare with t-table significant level 5%. Between two meanings (SEmxmy) = 0,78 this becomes t arithmetic result = 3,564. Then the result of the calculation is tested with table on degrees of freedom (dk) = (n1 + n2) - 2 = (10 + 10) - 2 and trust level 0,05 t count 2,101 (t-arithmetic = 3,564 > t-table = 2,101). Run 800 meters greatly influence the increase of lactic acid than the run 400 meters group.